Environmental enrichment decreases GABAergic inhibition and improves cognitive abilities, synaptic plasticity, and visual functions in a mouse model of Down syndrome - Begenisic, Tatjana; Spolidoro, Maria; Braschi, Chiara; Baroncelli, Laura; Milanese, Marco; Pietra, Gianluca; Fabbri, Maria Elena; Bonanno, Giambattista; Cioni, Giovanni; Maffei, Lamberto; Sale, Alessandro (Frontiers in Cellular Neuroscience, 2011)
Down syndrome (DS) is the most common genetic disorder associated with mental retardation. It has been repeatedly shown that Ts65Dn mice, the prime animal model for DS, have severe cognitive and neural plasticity defects due to excessive inhibition. We report that increasing sensory-motor stimulation in adulthood through environmental enrichment reduces brain inhibition levels and promotes recovery of spatial memory abilities, hippocampal synaptic plasticity and visual functions in adult Ts65Dn mice.